2017
DOI: 10.3847/1538-4357/aa8c77
|View full text |Cite
|
Sign up to set email alerts
|

Composite Spectral Energy Distributions and Infrared–Optical Colors of Type 1 and Type 2 Quasars

Abstract: We present observed mid-infrared and optical colors and composite spectral energy distributions (SEDs) of type 1 (broad-line) and 2 (narrow-line) quasars selected from Sloan Digital Sky Survey (SDSS) spectroscopy. A significant fraction of powerful quasars are obscured by dust and are difficult to detect in optical photometric or spectroscopic surveys. However, these may be more easily identified on the basis of mid-infrared (MIR) colors and SEDs. Using samples of SDSS type 1 and 2 matched in redshift and [O I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 149 publications
6
79
1
Order By: Relevance
“…Hickox et al (2017) showed that SED models are able to predict optical/mid-IR colors for obscured and unobscured quasars that are consistent with observations. The color cut used in DiPompeo et al (2017a) corresponds to the output of Hickox et al (2017) SED model that assumed A V = 20. Based on equation (3) in Draine (2003), this gives N H ∼ 3.7 × 10 22 cm −2 , which is consistent with our adopted definition of quasar obscuration.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Hickox et al (2017) showed that SED models are able to predict optical/mid-IR colors for obscured and unobscured quasars that are consistent with observations. The color cut used in DiPompeo et al (2017a) corresponds to the output of Hickox et al (2017) SED model that assumed A V = 20. Based on equation (3) in Draine (2003), this gives N H ∼ 3.7 × 10 22 cm −2 , which is consistent with our adopted definition of quasar obscuration.…”
Section: Introductionsupporting
confidence: 62%
“…Here, the black hole's change in mass determines the quasar's evolution from obscuration 1 We note that DiPompeo et al (2017a) defined quasar obscuration using an optical/mid-IR color cut of r − W 2 = 6 (Vega) (e.g., Hickox et al 2007Hickox et al , 2017 This cut takes advantage of the fact that obscured and unobscured quasars occupy different parts of SDSS/WISE color space (e.g., Hickox et al 2007). Hickox et al (2017) showed that SED models are able to predict optical/mid-IR colors for obscured and unobscured quasars that are consistent with observations. The color cut used in DiPompeo et al (2017a) corresponds to the output of Hickox et al (2017) SED model that assumed A V = 20.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the optically red source selection does not correspond to the same level of obscuring column densities as those seen for X-ray wavelengths. Hickox et al (2017) proposed an additional criterion for the selection of obscured AGNs based on the combination of the u and WISE W3 band. Since there is not a unique definition of how obscured an AGN must be to be classified as absorbed, the various selection criteria target different ranges of obscuration.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors (Jarrett et al 2011;Mateos et al 2012) have defined wedges in the WISE colour-colour plot (such as Figure 7) to idenfity AGNs. Hickox et al (2017) conclude that luminous quasars can be effectively selected using a simple criteria such as those identified by Stern et al (2012), although they warn that such criteria may miss heavily obscured quasars. In Figure 8, we plot the histogram of W1-W2 colours of all sources with redshift in our sample.…”
Section: Optical Identifications and Redshift Distributionmentioning
confidence: 98%